Penguatan Nilai Sosial Spiritual Melalui Poster Bagi Masyarakat Yang Terdampak Covid-19 di Kota Palangka Raya - Karliani, Eli; Mustika, Maryam; Triyani, Triyani; Tardimanto, Yuyuk (Abdi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This service activity was carried out in Menteng Palangka Raya Village for 4 months, starting from July to October with the following activity stages: 1). Observing the location and target of service to analyze target needs, namely in the Menteng Palangka Raya village, especially at the Covid-19 Isolation Center Hajj Dormitory Kel. Menteng; 2). Conducting FGDs with religious leaders (Islam, Christianity, Hinduism, Confucianism, Buddhism), and partners to analyze socio-spiritual values; 3). Making poster designs in accordance with social and spiritual values; 4). FGD design Social spiritual value poster with team and partners; 5. Carry out the service with an explanation of the poster to the Isolation Patient in the hajj dormitory, Menteng sub-district; 6). Conduct evaluation and reflection. The result of the service that has been carried out is the strengthening of spiritual social values that have been carried out for communities affected by COVID-19 in Menteng Village, namely through the installation of posters of spiritual social values installed in each self-isolation room and social media (Whatsapp Group of Covid-19 Patients), Facebook, Instagram with the aim of providing psychological reinforcement to patients affected by COVID-19 and strengthening the trust and optimism of all religious communities psychologically to recover for people who are isolating in that place and also posters in the form of banners aimed at the people of the city of Palangka Raya. The findings obtained from the results of the activity evaluation survey for Covid-19 patients in Menteng Village, Palangka Raya City, people who read the posters feel confident in God to recover, have concern for other patients to get well together, and have more faith in God Almighty by worshiping God. God, they are calmer and confident psychologically healed. Although there is an evaluation result that patients want that when they are isolated they are very worried about the family left at home.